2021
DOI: 10.1016/j.advwatres.2020.103812
|View full text |Cite
|
Sign up to set email alerts
|

Solute transport in bounded porous media characterized by generalized sub-Gaussian log-conductivity distributions

Abstract: There are increasing evidences that probability distributions and associated statistical moments of a variety of hydrogeological and soil science variables and their spatial increments display distinctive scale-dependent features that are not captured by a typical Gaussian model. A Generalized Sub-Gaussian (GSG) model is able to capture key aspects of this pattern. We present the results of a suite of computational analyses set in a Monte Carlo framework and aimed at assessing the impact of a GSG structure of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…In this study, we focus on the classical macrodispersive approach where the effect of system heterogeneity is addressed through the action of macrodispersion coefficients. The latter are conceptualized as attributes of the porous domain [1,3,12,17,18] in a way which is very similar to the case of thermal diffusivity. Thus, even as our study is keyed to mass transfer, the approach and strategy of analysis are readily transferable to settings entailing heat transfer in randomly heterogeneous porous media.…”
Section: Nomenclature Of Main Symbolsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we focus on the classical macrodispersive approach where the effect of system heterogeneity is addressed through the action of macrodispersion coefficients. The latter are conceptualized as attributes of the porous domain [1,3,12,17,18] in a way which is very similar to the case of thermal diffusivity. Thus, even as our study is keyed to mass transfer, the approach and strategy of analysis are readily transferable to settings entailing heat transfer in randomly heterogeneous porous media.…”
Section: Nomenclature Of Main Symbolsmentioning
confidence: 99%
“…Libera et al [34] provide a first numerical study on the effect of a GSG distribution of Y on concentration breakthrough curves at a well operating in a two-dimensional system. More recently, the role of the GSG nature of Y on transport behavior has been explored in [18] through a detailed suite of numerical Monte Carlo simulations within a laboratory column. Analytical solutions depicting transport in two-dimensional GSG domains are presented in [32] and [19].…”
Section: Nomenclature Of Main Symbolsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, the difference between statistics of c(x, t) obtained with diverse α values decreases as the travel time increases and as Pe decreases (see also Figure 3.b). We point out that the effect of α on the concentration breakthrough curve (BTC) in a single realization of the permeability field has been investigated in the past [46,57]. In general, the authors observed that decreasing the value of α yields (i) a delayed first time of arrival of the solute and (b) an increasing degree of asymmetry (and heavier tails) of the BTC.…”
Section: Resultsmentioning
confidence: 99%
“…In this work we investigate solute transport and the onset of anomalous or non-Fickian transport behaviour in high-contrast heterogeneous permeability fields, generated with the geostatistical pluri-Gaussian truncated (PGS) method (Mariethoz et al 2009). Solute transport has been widely investigated in continuous Gaussian and non-Gaussian permeability fields (Gotovac et al 2009;Sole-Mari et al 2021), and methods have also been proposed to handle non-continuous fields, suitable to reproduce geomaterials where property transition is marked by sharp interfaces (Bianchi and Pedretti 2017). PGS random fields are used in this context to model actual subsurface geological media in a sedimentary setting.…”
Section: Introductionmentioning
confidence: 99%